The calculation of the normalization factor in the multiproduct model of inventory management in the supply of two types of inputs to multiple intervals; Молодежь и современные информационные технологии; Т. 1 - Alimkhanova D. A. (Математическое моделирование и компьютерный анализ данных, 2014)
Заглавие с титульного экрана